Implications of SPLUMA in areas under rural traditional leadership in Mpumalanga province : the case of Bushbuckridge Local Municipality and Dr JS Moroka Local Municipality - Sambo, Tinyiko Ntombifuthi (My University, 2018)
“Although the bantustan system was abolished prior to the democratic transition, a sizable body of academic scholarship has asserted that this geography has left a lasting imprint upon rural areas” (King and Mccusker, 2006:1) The South African colonial and apartheid planning laws influenced the landscape of rural areas through fostering segregation, under-development, restrictions to land ownership and the establishment of the permission to occupy land. In post-apartheid South Africa, the government has tried to make strides to repeal and reverse the imprint which colonial and apartheid legislations left on the country. Yet, the process has not been without challenges, with Chapters 5 and 6 of the Development Facilitation Act, Act No.67 of 1995 (DFA) being declared unconstitutional in 2010. The DFA also had loopholes as it did not repeal colonial and apartheid planning legislations. Thus, modernist planning approaches were retained and continued to influence segregated land use management after 1995. Furthermore, the DFA by and large focused on the management of urban areas and did not subject rural areas to formalised land use management; irrespective of these areas practicing certain forms of land use practices. In order to bridge the gap in planning law, the Spatial Planning and Land Use Management Act, Act No.16 of 2013 commonly known as SPLUMA in the planning fraternity was enacted and assented into operation on the 1st July 2015. The new planning law is tasked with the responsibility of ensuring spatial justice through the incremental upgrading of informal areas by means of encouraging the “progressive introduction of administration, management, engineering services and land tenure rights to areas that are established outside existing planning legislation, and may include any settlement or area under traditional tenure” (SPLUMA, 2013:8). In light of the above, the research report explores the implications of SPLUMA in areas under rural traditional leadership with focus on two case studies respectively Bushbuckridge Local Municipality and Dr JS Moroka Local Municipality in Mpumalanga Province. The research report aims to understand the manner in which land use management can be incrementally introduced to rural areas from a modernist and post-modernist theoretical framework. The research rationale does not seek to resolve existing challenges as the study scope is limited, but explores the application of planning theory and practice on land use management within rural areas. The framing theory is informed by social theoretical analysis from different perspectives of dealing with traditional leadership, since traditional authorities continue to be influenced by planning law directly and indirectly. The modernist theoretical framework draws insight from theories on functionalism, liberalism and Marxism. Whilst post-modernism a subjective framing theory is informed by constructivism. The research is based on a qualitative research method informed by five key pillars respectively: desktop research influenced by grey literature; case studies as a means to compare research findings; interviews and observation sessions as a means of drawing experiences and insight from planning professionals in the public and private sector; mapping and photography. The primary focus of the qualitative research was on the case studies, aided by research interviews with municipalities, provincial sector departments and organisations that have either written or undertaken incremental land use planning in one form or another. The research sample comprised of twelve interviewees of which traditional authorities were not part of the sample mainly due their contestation on the implementation of SPLUMA. The research findings illustrate that the implementation of SPLUMA expands the traditional planning scope from focusing on urban areas, but by also focusing on areas previously excluded by planning. More critically that the planning profession needs to undertake research on indigenous knowledge in order to merge traditional and modern planning approaches in policy, tools and systems. Thus, the responsibility of ensuring spatial justice within rural areas cannot be solely achieved through land use management, but also needs to be accompanied by other land administration matters such as land tenure. The concept on incremental land use management is considered to be broad and vaguely discussed in SPLUMA.Thus; indepth research should be undertaken by provincial and national government to unpack the concept of incrementalism and its‟ practical implementation in areas previously excluded from planning processes. Furthermore, municipalities require political support and should also consider establishing land use structures/committees that operate within the traditional authority offices, aided by educational programmes on spatial planning and land use management.
A research report submitted in fulfilment of the requirements for the degree of Master of Science Town and Regional Planning to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2018
Keywords: Land use--South Africa--Planning; Rural development--South Africa; Local government--South Africa